Balloons Over Broadway : The True Story of the Puppeteer of Macy's Parade - Sweet, Melissa, 1956- (Boston, MA : Houghton Mifflin Books for Children, 2011)
Presents a tribute to the creator of the giant balloons that fill the sky during the Macy's Thanksgiving Day Parade, tracing the work of artist Tony Sarg, whose innovative "upside-down puppet" creations have become the parade's trademark.
Includes bibliographical references.
Keywords: Sarg, Tony, -- 1882-1942; Puppeteers -- Biography -- United States; Thanksgiving Day -- History -- New York (N.Y.); Parades -- History -- New York (N.Y.)